The combination of Q-switched neodymium:yttrium–aluminum–garnet (Nd:YAG) laser with photoacoustic pulse technology in combination with polynucleotides (PN) salmon DNA for skin rejuvenation: A case series - Setiawan , Stanley; Handayani , Theressia; Luziani, Stefani (Bali Dermatology Venereology and Aesthetic Journal, 2024)
Background: Skin aging leads to dyspigmentation, wrinkles, and lentigines. Photorejuvenation, especially Q-switched Nd:YAG laser therapy, is commonly used to address these concerns. We present a case series evaluating the effectiveness of combining Q-switched Nd:YAG laser with Polynucleotides (PN) Salmon DNA for facial photorejuvenation. Case series: Five healthy adults underwent four sessions of full-face laser toning with a QS 1064 nm Nd:YAG laser followed by Polynucleotide (PN) Salmon DNA 2% injections every two weeks. We recorded subjective assessments and pain levels during treatment and captured photographic images for analysis. The treatment significantly improved skin brightness and pigmentation, with some subjects achieving mild or no pigmentation. Skin elasticity improvements varied among subjects. Some experienced significant enhancement, while others showed minor changes or none at all. Skin redness responses varied. Objective measurements revealed pore size, skin elasticity, moisture, skin tone, wrinkles, and skin age improvements. Conclusion: Combining Q-switched Nd:YAG laser with PN Salmon DNA shows promise for enhancing skin health and appearance.